Quality of leisure time in dorms from students’ perspective - Milanović, Nedeljko M.; Stevanović, Nenad (Sociološki pregled, 2020)
The article deals with the issue of the quality of leisure time from the perspective of high school students who are accommodated in dorms. The article presents the results of the empirical research aimed at examining students’ opinions about leisure activities in the dorm, based on when it would be possible to make improvements in leisure time in the students’ dorm. The sample included 198 respondents, 113 female and 85 male, aged 15 to 18 years. For the purposes of this research, a descriptive method was used, as well as a survey technique. The interpretation of the obtained results leads to the conclusion that there is a significant degree of dissatisfaction with the quality of leisure activities offered to students in the dorm and the prevailing opinion is that leisure time in the dorm should be improved and innovated. Innovations and measures students propose to improve leisure time in the dorm are organizing trips, watching selected movies, arranging a room with board games, organizing themed evenings, greater commitment to sports activities, introducing new clubs and debates on a particular topic. These activities include the primary functions of leisure time: rest, entertainment and personality development of students. The results of this research indicate that leisure time in the dorm and activities that students engage in, should be paid significant attention from the pedagogical aspect and this segment of life in the dorm should be made more meaningful and of better quality.
Keywords: leisure time; leisure activities; high school students; dorm